Controlling size and size distribution of electrohydrodynamically prepared microbubbles - Farook, U; Stride, E; Edirisinghe, M (2009)
There are several methods for producing commercial quantities of coated microbubbles with diameters <10 μm and a low polydispersivity index for use as ultrasound contrast agents, drug and gene delivery vehicles. Co-axial electrohydrodynamic microbubbling is a recently developed method which can generate microbubbles at a high rate. In this method, two capillary needles are concentrically aligned and subjected to a potential difference applied between the needles and a ground electrode with a stream of gas pushed through the inner needle and a stream of liquid through the outer so that a two-phase jet is formed at the outlet. The jet breaks up into microbubbles which are collected in a suitable liquid. In this work, co-axial electrohydrodynamic microbubbling was used to prepare microbubbles from a phospholipid suspension containing 2 wt-% Tween 80, a surfactant. Microbubbling was carried out under different electrical fields and air/liquid flowrates in order to prepare microbubbles with a low polydispersivity index. At the ambient temperature, the microbubbles collected in distilled water had a mean diameter of ∼5 μm with a polydispersivity index of ∼9% and were stable for >18 h. © 2009 Institute of Materials, Minerals and Mining.